Web-Based Kupang Sales Information System - Helen Rindy Affikasari; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2022)
Kupang is a food that comes from the sea which contains various health benefits. Kupang is a type of shellfish that lives in the sea. This type of shellfish has a fairly high nutritional content, but unfortunately not everyone knows the content contained in mussels. And sometimes it's just made into processed food with soup without any innovation. The obstacle experienced by the seller of the village of Balnggabus is that the customer must come directly to the location to get the desired Kupang. Another problem faced is that customers are often disappointed because the supply of mussels has run out or when the seller is not selling. With a web-based sales information system, Kupang sales can reach a wider range of consumers and make it easier for consumers to make transactions.